Menelusuri Jejak-Jejak Peninggalan Islam di Sumatera Utara (Abad ke-13 hingga ke-20) dalam Perspektif Sejarah dan Sosial Tahun 2024 - Yudi Roswandi; Elianti Napitupulu; Maretta Ginting; Sarah Kholijah; Ekel Ginting (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
This article examines the development of Islam in North Sumatra through various existing historical remains, including mosques, tombs and local traditions related to the history of the spread of Islam from the 13th century to the 20th century. This research aims to provide an understanding of how Islam spread and integrated with local traditions in the region. The method used in this research is historical research through the stages of heuristics, source criticism, interpretation and historiography. The research results show that North Sumatra has a number of important historical remains, such as the Al-Mashun Grand Mosque, Maimun Palace, Azizi Tanjung Pura Mosque, and other historical tombs which are clear evidence of the spread of Islam in this region. This research also shows the important role of the Deli, Langkat and Asahan Sultanates in introducing and developing Islam, as well as how Islam adapted to local culture in North Sumatra. These findings provide an important contribution to understanding the history of Islam in Indonesia and the need to preserve historical remains as part of the nation's cultural heritage.